EFFECTS OF INDIVIDUAL INSOLVENCY AND PPIRP (PRE-PACKAGED INSOLVENCY RESOLUTION PROCESS) ON THE INDIAN BUSINESS ENVIRONMENT - Anand, Manoj Kumar; Sharma, Rajiv (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The introduction of the Insolvency and Bankruptcy Code (IBC), 2016 marked a paradigm shift in India’s insolvency framework. While corporate insolvency has received significant attention, the frameworks for individual insolvency and the Pre-Packaged Insolvency Resolution Process (PPIRP) are emerging mechanisms aimed at easing debt resolution. This paper explores the implications of individual insolvency and PPIRP on India’s business environment, with a focus on micro, small, and medium enterprises (MSMEs), financial institutions, and entrepreneurial risk-taking. The paper analyses policy developments, legal challenges, and stakeholder impact while offering suggestions for more effective implementation.